INFLUENCE AND STUDY OF MEDICINAL PLANTS OF UZBEKISTAN ON THE IMMUNE SYSTEM - Расулов Ф. Х.; Борецкая А. С.; Маматкулова М. Т.; Рузибаева Ё. Р. (Web of Journals Publishing, 2024)
In medicine, there are many infectious diseases that the immune system begins to fight when they (the pathogen) enter the body. The effectiveness of the immune system's response largely depends on its condition (immune status). The importance of some medicinal plants is great for the stability of the immune system and the effective fight against foreign genes. Modern advances in medicine have made it possible to identify diseases that depend on the quantity and quality of cells of the immune system. In the treatment of such diseases of the immune system, positive results are obtained from the use of traditional medicine prepared from medicinal plants. The study examined the effect of medicinal plants on phagocytic neutrophil cells of the immune system.
Keywords: Infectious diseases, immune status, medicinal plant, phagocytosis, neutrophil